Burundi : Joint Staff Advisory Note of Poverty Reduction Strategy Paper Preparation Status Report. (IMF Staff Country Reports; Country Report ;, 2005)
The Joint Staff Advisory Note (JSAN) of the Poverty Reduction Strategy Paper (PRSP) Preparation Status Report (PSR) on Burundi explains progress in developing the full PRSP as set out in the PSR. The PSR describes the actions that have been taken, or are under way, with the support of technical assistance, to improve the information base on the prevalence, characteristics, and perceptions of poverty in Burundi. The PSR also describes the considerable progress that has been achieved in improving the government's capacity to monitor and evaluate public social expenditures and other poverty-reducing outlays.